Constitutive model for predicting stress response of sulphur vulcanised rubbers during simultaneous deformation and chemical ageing - Ghosh P; Caruthers J M (156th ACS Rubber Division Meeting 1999. Conference preprints, Orlando 21st to 23rd Sep 1999.)
Sulphur vulcanised rubber is one of the earliest thermosetting polymers, yet still contnues as a major engineering material to this day. During the lifecycle of a vulcanised part, it can experience a complex deformation, thermal and cure histrory where the mechanical response of the part is often critical. Existing three-dimensional constitutive models for rubber elasticity implicitly assume the chemical composition of rubber is static and hence the mechanical response of the material is not coupled to any ongoing chemical reaction. However this is often and unrealistic assumption because polymer network can undergo scission and reformation with time, especially in chemically aggressive environments. A framework for solving the coupled rubber-chemistry/rubber-mechanics problem by incorporating the detailed microstructural information from the vulcanisation chemistry into the consecutive equations is outlined. Specifically, the stress is assumed to be a linear superimposition of the stresses originating from a family of networks, where each rubber network is assumed to have an undeformed reference configuration when the crosslinks are created. A quantitative population balance based kinetic has been developed to describe accelerated sulphur vulcanisation, and this kinetic model is now connected to the three dimensional constitutive model for rubber elasticity. The resulting constitutive model for simultaneous cure and deformation are demonstrated for a particular isothermal, uniaxial deformation history for a sulphur-vulcanised NR cured with MBS accelerator.
Source Year: 2000
Keywords: Chemical ageing; Stress response; Sulphur vulcanised rubber